2012
DOI: 10.1371/journal.pone.0029660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Molecular Weight Heparins (LMWHs) on antiphospholipid Antibodies (aPL) – Mediated Inhibition of Endometrial Angiogenesis

Abstract: Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by vascular thrombosis and/or pregnancy morbidity in the presence of circulating antiphospholipid antibodies (aPL). Different pathogenic mechanisms for aPL-mediated pregnancy failure have been proposed. In particular a direct effect of aPL on both maternal and fetal side of the placental tissue has been reported, since their reactivity with β2-glycoprotein I (β2GPI) makes them adhere to trophoblast and human endometrial endothelial cell (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
(71 reference statements)
1
35
1
1
Order By: Relevance
“…Furthermore, in vitro coexposure of serum of high-risk women with LMWH restored endothelial tube formation, consistent with previous reports from our group and others. 20,21 These results illustrate a potential mechanism whereby LMWH could exert a beneficial effect on maternal endothelial function, as previously demonstrated in patients with coronary artery disease. 13,14 These observations are consistent with a previous trial demonstrating that LMWH therapy throughout pregnancy prevented the rise of systolic and diastolic blood pressure and resistance of uterine arteries in pregnant women at high risk of preeclampsia, in addition to reducing the recurrence of preeclampsia.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in vitro coexposure of serum of high-risk women with LMWH restored endothelial tube formation, consistent with previous reports from our group and others. 20,21 These results illustrate a potential mechanism whereby LMWH could exert a beneficial effect on maternal endothelial function, as previously demonstrated in patients with coronary artery disease. 13,14 These observations are consistent with a previous trial demonstrating that LMWH therapy throughout pregnancy prevented the rise of systolic and diastolic blood pressure and resistance of uterine arteries in pregnant women at high risk of preeclampsia, in addition to reducing the recurrence of preeclampsia.…”
Section: Discussionsupporting
confidence: 74%
“…In a mouse-in-vitro-system, HB-EGF has been demonstrated to promote [26]. It also increases the production of both prolactin and IGF-1, inhibits the production of IGFBP-1 that play a role in endometrial receptivity [22] [27].…”
Section: Khalife G Ghazeeri Open Journal Of Obstetrics and Gynecmentioning
confidence: 99%
“…Laboratory findings on endometrial cells were different from those found on other cell types. Anti β 2GP1 antibodies purified from APS patients were found to inhibit angiogenesis, VEGF secretion, and NF κ B activation in a dose-dependent way in endometrial cells [13, 14]. This implicates that pathological mechanisms of aPL can differ between various cell types which could explain variations in treatment efficiency.…”
Section: Pathogenesis Of Apl During Pregnancymentioning
confidence: 99%
“…(2) Mechanisms on endometrial cells [13, 14]Angiogenesis inhibitionDecrease in VEGF secretionNF κ B activation inhibition. …”
Section: Pathogenesis Of Apl During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation